2015
DOI: 10.1136/sextrans-2014-051987
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection in a clinic sample of transsexuals in Italy: Table 1

Abstract: The high rate of detectable HPV DNA by oncogenic types suggests that periodic cytological screening and clinical evaluation may be necessary since transsexuals are at high risk of anogenital cancer. Also promoting HPV vaccination in younger subjects may be advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…In a recent study, Loverro et al 10 reported on HPV prevalence in transgendered persons in Italy, in which one out of a total of eight women who underwent vaginoplasty tested positive for vaginal hrHPV. However, the number of included patients in this study is small, so the true clinical importance and burden of neovaginal HPV infections in transgender women in Europe remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Loverro et al 10 reported on HPV prevalence in transgendered persons in Italy, in which one out of a total of eight women who underwent vaginoplasty tested positive for vaginal hrHPV. However, the number of included patients in this study is small, so the true clinical importance and burden of neovaginal HPV infections in transgender women in Europe remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth case, with skin graft, was not tested for HPV; however, the immunostain for p16 turned out to be negative [4][5][6][7]. Transgender women have a high prevalence of sexually transmitted infections, with a HPV infection rate of 52.4%, all of which have at least one high-risk genotype [10][11][12][13][14]. This could be explained by several contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several small studies have determined the HPV burden in the transgender community to range from 40% to 95%, with the majority of the identified strains high risk for oncogenic potential. 31,[35][36][37] Furthermore, only 27% of transgender men responding to the 2015 U.S. Transgender Survey had a Pap smear in the past year, compared with 43% in the U.S. adult population, increasing the risk for undetected and persistent HPV. 38 The 2015 U.S. Transgender Survey identified that specifically among transgender men, only 14% had undergone hysterectomy and an additional 44% responded that they desired a hysterectomy in the future.…”
Section: Cervical Cancermentioning
confidence: 99%